2022
DOI: 10.3390/vaccines10091507
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Cytokines and Interferon-Stimulated Gene Responses Induced by Seasonal Influenza A Virus with Varying Growth Capabilities in Human Lung Epithelial Cell Lines

Abstract: In a previous study, we described the diverse growth capabilities of circulating seasonal influenza A viruses (IAVs) with low to high viral copy numbers in vitro. In this study, we analyzed the cause of differences in growth capability by evaluating pro-inflammatory cytokines (TNF-α, IL-6, IFN-β) and antiviral interferon-stimulated genes (ISG-15, IFIM1, and TRIM22). A549 cells (3.0 × 105 cells) were inoculated with circulating seasonal IAV strains and incubated for 6 and 24 h. In cells inoculated for 6 h, IAV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…To assess the role of more downregulated ISGs in sMDCK cells, we tested the effect of the suppression of JAK/STAT signaling by adding pyridone 6 (P6) during infection. P6 is a pan-JAK inhibitor and was verified to inhibit ISG expression through competitively binding to JAK1, JAK2, JAK3, and Tyk2 [ 32 , 42 , 43 , 44 ]. ISG expression levels were examined in P6-treated aMDCK and sMDCK cells.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the role of more downregulated ISGs in sMDCK cells, we tested the effect of the suppression of JAK/STAT signaling by adding pyridone 6 (P6) during infection. P6 is a pan-JAK inhibitor and was verified to inhibit ISG expression through competitively binding to JAK1, JAK2, JAK3, and Tyk2 [ 32 , 42 , 43 , 44 ]. ISG expression levels were examined in P6-treated aMDCK and sMDCK cells.…”
Section: Resultsmentioning
confidence: 99%
“…ISG15 plays a central role in host antiviral response [ 39 ]. In the case of influenza A virus infection, ISG-15 affects viral genome replication [ 40 ]. HNRNPH1 is an RNA-binding protein that forms complexes with heterogeneous nuclear RNA and participates in RNA editing, modification, and stability [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This upregulation could indicate that asymptomatic patients quickly recognized and responded to the virus with the help of plasmablast cells in the extrafollicular pathway. A recent study by Hinai et al (2022) (50) has shown that an increase in the expression of interferon stimulated genes reduces the viral copies of influenza A virus in vitro. The upregulation in interferon stimulated genes in asymptomatic COVID-19 patients was also found in other studies and was correlated with good clinical outcomes in these patients (51; 52).…”
Section: Discussionmentioning
confidence: 99%